Kahoot Improves Elementary Students Vocabulary Mastery in Experimental Study - Indah Putri Lestari; Yuli Astutik (Academia Open, 2025)
General Background: The integration of gamified digital tools in education has been widely recognized as a means to increase student engagement and motivation. Specific Background: Interactive platforms such as Kahoot provide time-based quizzes, instant feedback, and competitive elements that may support language learning in elementary classrooms. Knowledge Gap: Despite extensive research on motivation and general outcomes, limited empirical evidence addresses concrete linguistic gains, particularly vocabulary mastery among young learners. Aims: This study investigates whether Kahoot-based instruction leads to greater vocabulary acquisition than conventional teaching methods among fourth-grade elementary students. Results: Using a true experimental pre-test–post-test design with 36 students, both groups improved, but the Kahoot group achieved substantially higher gains, with a statistically significant difference in post-test scores (p = 0.012) and a large effect size. Novelty: The study contributes direct experimental evidence focusing on vocabulary mastery rather than engagement alone in elementary English education. Implications: The findings indicate that integrating game-based digital platforms into language instruction can support active participation and measurable vocabulary development, suggesting practical value for teachers seeking interactive approaches aligned with contemporary curricula. Highlights: Learners using interactive quizzes achieved markedly larger score gains than those taught with textbooks and worksheets. Both instructional approaches produced progress, but the digital game group demonstrated a substantially wider improvement margin. Statistical testing confirmed a significant difference between groups, indicating strong educational relevance of the treatment. Keywords: Kahoot; Gamified Learning; Vocabulary Mastery; Elementary English Education; Experimental Study